Metals levels and human health risk assessment in eight commercial fish species collected from a market, Wuhan, China - Yin, Jiaojiao; Cheng, Liangyu; Jiang, Xiaoming; Wang, Li; Gao, Pan; Zhong, Wu; Zhang, Xuezhen (Frontiers in Sustainable Food Systems, 2024)
In this study, a comprehensive analysis utilizing inductively coupled plasma mass spectrometry (ICP-MS) was conducted to investigate the distribution of tissues (dorsal muscle, ventral muscle and head) and perform a health risk assessment of nickel (Ni), copper (Cu), zinc (Zn), cadmium (Cd) and lead (Pb) in 8 fish species (Ctenopharyngodon idellus, Megalobrama amblycephala, Hypophthalmichthys molitrix, Hypophthalmichthys nobilis, Carassius auratus, Cyprinus carpio, Culter alburnus and Lateolabrax japonicas) collected from the Baishazhou market with different trophic levels and habitat preference. The levels of metals exhibited variation among different fish tissues and species, showing an order of Zn > Cu > Ni > Pb > Cd. In terms of tissues, fish head demonstrated a greater capacity for metal accumulation compared to the muscles. Regarding fish species, the extent of accumulation ability varied depending on the specific metal, exhibiting the following order according to metal pollution index (MPI): H. molitrix (0.568) > C. auratus (0.508) > M. amblycephala (0.469) > C. idellus (0.336) > C. alburnus (0.315) > C. carpio (0.274) > L. japonicus (0.263) > H.nobilis (0.206). Furthermore, in accordance with the results of health risk assessment, there was no potential health risk associated with the consumption of these fish species, as all target hazard quotient (THQ) values (ranger from not detected to 0.192) were below 1, and the maximum hazard index (HI) value was observed in C. carpio (0.519 for adults, 0.622 for children). These results in this study indicate there were no potential health risk associated with consuming these fish bought from the market.